Generation of the Study Program "Precision Mechatronic Design" of the Technological Institute of Hermosillo, Under the Competency-Based Curriculum Model (Docentes 2.0 Journal, 2020)
The demand of the labor market within the industry, as well as the changing globalized market, increasingly require engineers with adaptable and changing qualities, especially in focused commercial sectors, where technical and scientific knowledge are of high importance, which make Engineer a human capital of great value for the industrial sector. At the educational level, within the Technological Institutes attached to the National Technological Institute of Mexico, teaching-learning systems that meet industrial needs are sought, so that academies work together with the government sector and the productive sector, to adapt the models education in specialties according to the needs of the regional and national commercial sector. The objective of this research is to project and elaborate the subject of “Precision mechanical design” for the Mechatronics Engineering specialty of the Technological Institute of Hermosillo, called “Mechatronic design for the aerospace and automotive industry”, based on the competency model and the previous analysis of industrial needs.
Keywords: Curriculum model; competencies; curriculum; engineering specialty